Digenea (Trematoda) of Micropogonias furnieri (Desmarest) (Perciformes, Sciaenidae) from Rio Grande do Sul, Brazil - Pereira Jr,Joaber (2000)
Micropogonias furnieri (Desmarest, 1823) from the coast of Rio Grande do Sul State were examined and six trematodes species were recovered: Aponurus laguncula Looss, 1907, A. pyriformis (Linton, 1910), Monascus filiformis (Rudolphi, 1819), Opecoeloides catarinensis Amato, 1983, O. stenosomae Amato, 1983, and Pachycreadium gastrocotylum (Manter, 1940). All species are registered for the first time in Rio Grande do Sul State and M. furnieri represents a new host record for A. laguncula, A. pyriformis and M. filiformis.